The Communicational Paradigm of the Information Society: The case of Media Pluralism in Europe and in Latin America - Verschakelen, Jeroen (2013)
Whereas the development of Information Society has caused a deep change in the communicational paradigm of the twentieth century, the predominance of neoliberal economic policies has allowed a significant market concentration. All at national, regional and international levels, both in Europe and in Latin America, policy makers have responded to these two factors, designing policies that are aimed at allowing not only individual’s freedom of expression but also pluralism in a field where digitalization and convergence can only enhance the effects of economic concentration. In the following paragraphs we analyze the case of Media Pluralism since it appears to be a meaningful example of what has, has not and should be done in order to face the expected and emerging consequences of the ongoing changes.